2023
DOI: 10.3390/medicina59030521
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anemia-Related Early Childhood Caries on Parents’ and Children’s Quality of Life

Abstract: Background and Objectives: Today, oral diseases are well-known for their effects, not only on daily life but also on quality of life (QoL). Dental caries, especially early childhood caries (ECC), are considered a public health concern as regards their impact on the life quality of children and parents from multiple aspects. The present research was conducted to assess the effect of anemia on oral-health-related quality of life (OHRQoL) in terms of children and parents. Materials and Methods: The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Schroth colleagues compared Severe ECC children with caries free children and found lower mean Hb in children with Severe ECC, and 6 times greater odds of iron deficiency anemia compared to caries free children 23. Similarly, Tang and colleagues reported more than 7 times greater odds of anemia in children with higher number of carious tooth surfaces (>35 DEFS) compared to those having lesser number of affected tooth surfaces (<35 DEFS) 23 . Study used a different modelling approach and observed that caries severity is higher in children with anemia, which is consistent with these previous studies 24 Our information was collected through the child's mother, this was an advantage as direct interaction was done. Our study was conducted within a single community, due to which we cannot translate our findings to other low income communities.…”
Section: Resultssupporting
confidence: 83%
“…Schroth colleagues compared Severe ECC children with caries free children and found lower mean Hb in children with Severe ECC, and 6 times greater odds of iron deficiency anemia compared to caries free children 23. Similarly, Tang and colleagues reported more than 7 times greater odds of anemia in children with higher number of carious tooth surfaces (>35 DEFS) compared to those having lesser number of affected tooth surfaces (<35 DEFS) 23 . Study used a different modelling approach and observed that caries severity is higher in children with anemia, which is consistent with these previous studies 24 Our information was collected through the child's mother, this was an advantage as direct interaction was done. Our study was conducted within a single community, due to which we cannot translate our findings to other low income communities.…”
Section: Resultssupporting
confidence: 83%
“…The findings are crucial for clinical decision-making, offering guidance on selecting appropriate desensitizing agents to ensure the optimal retention of dental prostheses [ 29 ]. The article “The Impact of Anemia-Related Early Childhood Caries on Parents’ and Children’s Quality of Life” by Dila Özyılkan et al [ 30 ] explores the relationship between anemia-related dental caries in children and their quality of life, as well as that of their parents. Utilizing the Early Childhood Oral Health Impact Scale (ECOHIS) and the Parental-Caregivers Perceptions Questionnaire (P-CPQ), the study assesses the impact of these dental issues on children and parents.…”
mentioning
confidence: 99%
“…Utilizing the Early Childhood Oral Health Impact Scale (ECOHIS) and the Parental-Caregivers Perceptions Questionnaire (P-CPQ), the study assesses the impact of these dental issues on children and parents. The findings highlight the significant negative impact of anemia-related dental caries on quality of life, underscoring the importance of prioritizing preventive measures and timely dental treatments for affected children [ 30 ].…”
mentioning
confidence: 99%
“…The Impact of Anemia-Related Early Childhood Caries on Parents' and Children's Quality of Life (16).…”
mentioning
confidence: 99%
“…The present research was conducted to evaluate the effect of anemia on oral health-related quality of life (OHRQoL) in terms of children and parents (16). 13 PubMed Transversal study Impact of dental caries on oral health-related quality of life in children with dental behavior management problems (17).…”
mentioning
confidence: 99%

Early childhood caries and its impact on general health: Narrative review

Mireya Catalina León Abad,
Michelle Bridget Guerrero Andrade,
Tutora Fernanda de Lourdes Cárdenas Vidal
2024
World J. Adv. Res. Rev.